Analisis Kinerja Website Pemerintah Kota Pekalongan - Mohammad Reza Maulana; Eko Budi Susanto; Sattriedi Sattriedi (JURNAL LITBANG KOTA PEKALONGAN, 2021)
The Pekalongan City Government has an official website as a form of service to the community. Website is one form of implementation of E-Government. Website maintenance and repair needs to be done regularly to improve services to the community. There are so many visitors, of course, it becomes a problem when simultaneously accessing a website. For this reason, it is necessary to carry out a work analysis from the Pekalongan City Government website. In analyzing the Pekalongan City Government website, this study used performance testing especially using load testing with several variables including Internet speed, threads (virtual users), ramp-up period, repetition. The tool used to perform the analysis is JMeter. The results of the tests carried out are: for an access speed of 1.8 MBps, the server can only serve about 16.8 requests every minute. This of course can cause the website to go down which ultimately cannot be accessed when visited by many visitors. Keywords: Performance testing, load testing, JMeter.